Uji Aktivitas Antibakteri Kombinasi Ekstrak Etanol Daun Sirih Hijau (Piper betle L.) dan Madu terhadap Bakteri Propionibacterium acnes - Nurul; Fajar; Lucia Bilasonya Sakramentia (Proceeding of Mulawarman Pharmaceuticals Conferences, 2019)
Green betel leaf (Piper betle L.) and honey have been scientifically known to have antibacterial activity. The antibacterial activity of green betel leaf is caused by the presence of compounds, such as tannins, flavonoids, saponins, alkaloids, and terpenoids. While honey is due to the high sugar content, the acidity and compounds from the flavonoid, glycoside, and hydrogen peroxide groups. This study aims to determine the antibacterial activity of the combination of these extracts against Propionibacterium acnes. Antibacterial activity was tested using the well technique agar diffusion method with green betel leaf extract concentrations of 2.5%, 5%, 7.5%, 10%, and 12.5% ??and combined each concentration with 100% of honey. The results obtained by the extract antibacterial activity at concentrations of 2.5%, 5%, 7.5%, 10%, and 12.5%, each combined with 100% of honey respectively at 11,81 mm; 14,45 mm; 15,48 mm; 16,77 mm; and 14,68 mm against Propionibacterium acnes. The results of this study indicate the combination of green betel leaf extract with a concentration of 10% and 100% honey produces the most effective inhibition zone.